The world's greenest buildings : promise versus performance in sustainable design - Yudelson, Jerry; Meyer, Ulf, 1970- (New York : Routledge/Taylor & Francis Group, 2013)
'The World's Greenest Buildings provides the first way to compare building performance, using cost and energy use data that has been verified by independent third parties and to understand how building performance can be upgraded. The book provides: an overview of the rating systems and shows'best in class' building performance in North America, Europe, the Middle East, India, China, Australia and the Asia-Pacific region practical examples of best practices for greening both new and existing buildings, useful for architects and engineers, contractors, building owners and managers, facility professionals, developers, lenders and investors, brokers and appraisers, and everyone charged with managing commercial and institutional buildings a response to the intense need for a practical reference for design professionals, building owners, developers and facility managers on how green buildings actually perform at the highest level, one that takes them step-by-step through many different design solutions. interviews with architects, engineers, building owners and developers and industry experts, to provide added insight into the greening process a complete guide to world-class green building performance primarily for new buildings, including corporate, commercial, educational, governmental and other large building types a welath of exemplary case studies of successful green building projects using actual performance data from which to learn a'recipe,' based on others' experiences, for delivering successful green building projects in the various countries profiled'--
Includes bibliographical references (pages 239-255) and index.
Keywords: Sustainable buildings -- Evaluation; Buildings -- Performance